The Effectiveness of SFBC Group Counseling with Exception Question and Miracle Question Techniques to Improve Self-Adjustment of Students at MTs Negeri 1 Palembang - An-Nur Pasha Ramadhan; Mungin Eddy Wibowo; Sugiyo (EMPATI: Jurnal Bimbingan dan Konseling, 2026)
This study aims to determine the effectiveness of group counseling using the Solution-Focused Brief Counseling (SFBC) approach, with the Exception Question and Miracle Question techniques, in improving students' self-adjustment at MTs Negeri 1 Palembang. The research employed an experimental method with a Randomized Pretest–Posttest Comparison Group Design, involving 21 seventh-grade students divided into three groups: the Exception Question, the Miracle Question, and a control group. The instrument used was a self-adjustment scale that had been tested for validity and reliability. Data were analyzed using the Wilcoxon Signed-Rank Test to assess effectiveness within each group and the Kruskal-Wallis Test to examine differences in effectiveness among groups. The findings show that both techniques effectively improved students' self-adjustment, with the Miracle Question technique demonstrating a stronger effect. These results indicate that SFBC, particularly the Miracle Question technique, can be an effective intervention to enhance students' self-adjustment